Hubungan Antara Dukungan Pemerintah Desa Dengan Partisipasi Masyarakat Dalam Pelaksanaan Pendidikan Nonformal Didesa Marunggi - Silvia Septriani Putri; Vevi Sunarti (Universitas Negeri Padang, 2022)
This research is motivated by Community Participation in the Implementation of Education that has not run optimally in Marunggi Village, Pariaman City. There is still a lot of non-formal education that has not been implemented and many face problems. This research is a quantitative type of correlational research. Community participation in education is very low, but community participation in education is very important because whatever is produced not through community involvement in the entire process will result in a lack of sense of ownership and responsibility for them to participate in implementing and maintaining the continuity of education. The population in this study was 113 people and the sample of this study was 53 people who were enrolled in non-formal education programs with the sampling technique of cluster random sampling. The analysis of this research is Pearson product moment correlation. There is a significant relationship between government support for community participation in the implementation of non-formal education in Marunggi village, Pariaman City